Answer: The solutions are:
x1 = (- 9 + √17)/8 = -0.6
x2 = (-9 - √17)/8 = -1.6
Step-by-step explanation:
We have the equation:
4*x^2 = -9x - 4
first we put all the terms in one side of the equation:
4x^2 + 9x + 4 = 0
now, we use the Bhaskara's equation to find the roots:
where for a function:
ax^2 + bx + c = 0
the roots are:
x = (-b +- √(b^2 - 4ac))/2a
where each root takes one of the possible signs of the square root.
so, in our case we have:
x = (-9 +- √(9^2 - 4*4*4))/(2*4) = (- 9 +- √17)/8
then the solutions are:
x1 = (- 9 + √17)/8 = -0.6
x2 = (-9 - √17)/8 = -1.6